Black phosphorus: A novel nanoplatform with potential in the field of bio-photonic nanomedicine - Taojian Fan; Yansheng Zhou; Meng Qiu; Han Zhang (Journal of Innovative Optical Health Sciences, 2018)
Single- or few-layer black phosphorus (FLBP) has attracted great attentions in scientific community with its excellent properties, including biodegradability, unique puckered lattice configuration, attractive electrical properties and direct and tunable band gap. In recent years, FLBP has been widely studied in bio-photonic fields such as photothermal and photodynamic therapy, drug delivery, bioimaging and biosensor, showing attractive clinical potential. Because of the marked advantages of FLBP nanomaterials in bio-photonic fields, this review article reviews the latest advances of biomaterials based on FLBP in biomedical applications, ranging from biocompatibility, medical diagnosis to treatment.